1997
DOI: 10.1103/physreva.56.543
|View full text |Cite
|
Sign up to set email alerts
|

Resonance formation of hydrogenic levels in front of metal surfaces

Abstract: The electronic self-energy of hydrogenic ions interacting with a jellium metal surface is studied within the fixed-ion approximation. A model framework is introduced that allows for the efficient computation of the complex ͑non-Hermitian͒ self-energy matrix in a large space of ͑bound͒ hydrogenic states. For the specific case of protons interacting with an aluminum surface, resonance energies and widths of dressed ionic states are obtained by diagonalizing the self-energy matrix. The hybridization properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Since the initial state |Ψ(t = 0) = |Ψ F − is orthogonal to the vector |Q , i.e., it is in the physical subspace, we can omit the projection operators to the left and right of the exponential in (11). So in (11) we take…”
Section: Wave Packet Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial state |Ψ(t = 0) = |Ψ F − is orthogonal to the vector |Q , i.e., it is in the physical subspace, we can omit the projection operators to the left and right of the exponential in (11). So in (11) we take…”
Section: Wave Packet Propagationmentioning
confidence: 99%
“…Since a few years the development of accurate theoretical approaches to the RCT in the case of free electron metal surfaces [5][6][7][8][9][10][11] has led to a successful description of a one-electron transfer in the interaction of ions (atoms) with such surfaces [12][13][14]. All these approaches are based on the description of single electron being transferred between the atom and the surface.…”
Section: Introductionmentioning
confidence: 99%
“…For the particular case of H − interacting with Cu(111) metal surfaces, which support an L-band gap, it was demonstrated that for long ion-surface interaction times the active electron has enough time to respond sensitively to details of the substrate electronic structure and that the electronic dynamics of the collision system evolves adiabatically, consistent with the fixed-ion approximation [6][7][8]. In contrast, for short interaction times, details of the substrate electronic structure are not resolved, and the time evolution of the collision system is well described by a structureless jellium model for the target electronic distribution [9].…”
Section: Introductionmentioning
confidence: 86%
“…1). Resonant processes, being one-electron ones, have been described abundantly in the literature, practically for any atom/solid combination, using different techniques [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%